Maple syrup urine disease diagnosed in a resource-limited setting in an infant in Nepal: a case report - Sujata Baidya; June Thapa; Anuradha Kadel; Nikita Kharal; Machhindra Lamichhane; Raju Kumar Dubey; Mithileshwer Raut; Aseem Bhattarai; Eans Tara Tuladhar; Vijay Kumar Sharma; Apeksha Niraula (BMC, 2024)
Abstract Background Maple Syrup Urine Disease (MSUD) is a rare inherited disorder of metabolism, which manifests early in life in classical forms. Recurrent illness and exertion aggravate neurotoxicity. This case highlights MSUD diagnosed in association with COVID-19 complications from Nepal. Case presentation We present a case of a 4-month-old child with a biochemical diagnosis of flared-up MSUD. Initially presenting with chief complaints of fever, noisy breathing, chest retraction, cough along with lethargy and poor feeding since the first week of life, the child also had developmental delay with feeble neck holding and absent social smile. The child was diagnosed with COVID-19 pneumonia and admitted in the Intensive Care Unit, requiring mechanical ventilation for 12 days. Despite the clinical resolution of pneumonia, the child had multiple episodes of generalized seizures and was sickly and frail. An incessant peculiar odor emanating from the child led to strong suspicion of metabolic disorder. Qualitative screening for amino acids (FeCl3 and 2,4-dinitrophenylhdrazine/DNPH) in urine and further gas chromatography-mass spectrometry revealed increased branched-chain amino acids(valine, leucine, and isoleucine). With dietary restrictions, the child was doing well. However, unfortunately, after 10 days of discharge, the child succumbed to death. Conclusions This case highlights the outpouring of hidden metabolic disorders with the onset of new diseases. It could have been detected and managed earlier with expedited neonatal screening and proper intervention.